Institutional Integrity and Quality Assurance in Teaching and Learning Practices at Public Universities in Nigeria - Olugbenga Ajadi (International Journal of Education and Teaching Zone, 2026)
This study examined the causes and types of academic misconduct and their relationship with institutional integrity in public universities in Southwest Nigeria. A total of 450 academic staff, non-academic staff, and students from three selected public universities were recruited using purposive, stratified, and disproportionate sampling techniques. Data were analyzed using descriptive statistics and Pearson's product-moment correlation. The findings identified examination malpractice, plagiarism, and academic dishonesty as the most prevalent forms of misconduct, while weak accountability and governance transparency emerged as the primary contributing factors. The reliability of the questionnaire was established using Cronbach's alpha, yielding coefficients of 0.84, 0.81 and 0.88 for perception, types of academic misconduct and institutional integrity and academic misconduct respectively.  The survey found among sampled students and staff, inadequate accountability mechanisms (84.7%, mean = 4.24) and governance transparency deficits (80.0%, mean = 4.12) significantly contributed to academic misconduct. The study also found moderate negative relationship between academic misconduct and institutional integrity (r = -0.482, p < 0.01). The coefficient of determination (r² = 0.232) showed that institutional integrity explained 23.2% of academic misconduct variance, indicating a moderate-to-large effect. The study concluded that institutional integrity requires stronger accountability and transparency, but findings may be affected by social desirability bias in self-reported data.